Non-invasive assessment of cerebral hemoglobin parameters in intracranial dural arteriovenous fistula using functional near-infrared spectroscopy—A feasibility study - Senthilvelan, Santhakumar; Kannath, Santhosh Kumar; Arun, Karumattu Manattu; Menon, Ramshekhar; Kesavadas, Chandrasekharan (Frontiers in Neuroscience, 2022)
Purpose The purpose of this study was to assess the feasibility of non-invasive assessment of cerebral hemodynamics using functional near-infrared spectroscopy (fNIRS) in patients with intracranial dural arteriovenous fistula (DAVF) and to correlate the hemodynamic changes with definitive endovascular treatment. Methodology Twenty-seven DAVF patients and 23 healthy controls underwent 20-mins task-based functional near-infrared spectroscopy and neuropsychology evaluation. The mean change in the hemoglobin concentrations obtained from the prefrontal cortex was assessed for oxyhemoglobin, deoxyhemoglobin, and oxygen saturation (HbO, HbR, and SO2, respectively). The fNIRS data were analyzed and correlated with improvement in neuropsychology scores at 1-month follow-up. Results There was a significant reduction in HbO in the patient group, while it increased in controls (−2.57E−05 vs. 1.09E−04 mM, p < 0.001). The reduced HbO significantly improved after embolization (−2.1E−04 vs. 9.9E−04, p = 0.05, q = 0.05). In patients with aggressive DAVF (Cognard 2B and above), the change was highly significant (p < 0.001; q = 0.001). A moderate correlation was observed between MMSE scores and HbO changes (ρ = 0.4). Conclusion fNIRS is a useful non-invasive modality for the assessment of DAVF, and could potentially assist in bedside monitoring of treatment response.